2011
DOI: 10.1088/0022-3727/44/35/355203
|View full text |Cite
|
Sign up to set email alerts
|

Ion emission in collisions between two laser-produced plasmas

Abstract: Measurements of the total ion emission from a pair of colliding laser-produced aluminium plasmas were obtained with the aid of a Faraday cup detector. The energy profile width at half height of the kinetic energy distribution for ions emitted normal to the target was found to be 30% narrower for colliding plasmas compared to a single plasma. Similar to ion emission from single plumes, the mean ion kinetic energy is observed to increase with the energy of the incident laser pulse. However, the width of the ion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…This were captured via a intensified charged coupled device (ICCD). 25 a focused beam strongly influences the expansion rate, degree of ionization, ionic yield, and recombination rates within the early phases of the rapidly expanding laser plasma plume. 28 Figure 2 shows the recorded Faraday cup TOF current trace for all elements studied in single plume (S p ) mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This were captured via a intensified charged coupled device (ICCD). 25 a focused beam strongly influences the expansion rate, degree of ionization, ionic yield, and recombination rates within the early phases of the rapidly expanding laser plasma plume. 28 Figure 2 shows the recorded Faraday cup TOF current trace for all elements studied in single plume (S p ) mode.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid divergence of the V TOF 2 profiles as the atomic mass decreases is further evidence of the influence of mechanisms within the stagnation layer, which result in the unique dynamics of colliding plasma plumes, and these mechanisms scale with decreasing atomic mass. Indeed electrostatic studies of colliding laser plasma plumes [23][24][25] have all reported on the notable K e energy and profile width at half maximum (PWHM) of C p plumes. Assuming a sufficiently small mean free path for both ions and electrons (k ee , k ii < 5 lm), 1 stagnation layer dynamics are collisionally dominated, and this highly localized region can exhibit a jump in the local electron density (N e ) by a factor of $5 in comparison to the seed plasmas.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…So we evaluated the ion flux as well as velocities of single plasmas and the attenuation of the ion signal due to plasma shielding using a Faraday cup. Ion analysis employing FCs is one of the easiest technique to implement 1,34,35 and it provides significant information of the charge-integrated ion flux, ion temporal profiles, and hence kinetic energy distributions. Ion emission temporal-profiles from single and colliding plasmas of the four targets used, viz., W, Mo, Al, and C were collected and are given in Figs.…”
Section: B Ion Emission Analysismentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Despite extensive experimental and theoretical progress in the dynamics of single laser produced plasmas (LPPs), little attention has been paid to the study of the nature and dynamics of laser-produced colliding plasmas even though several new applications are emerging. Several target geometries and configurations [10][11][12][13][14] have been used for generating and investigating colliding plasmas where a number of observations were reported and parameters determined such as changes in the kinetic energy of the ablated species and the degree of their ionization.…”
Section: Introductionmentioning
confidence: 99%